SECURITISATION AND ITS IMPLEMENTATION IN TURKEY - Gecer, Abdullah (2006)
Annual issuance of asset backed securities reached to $3.650 billion globally at the end of 2005 and the securitisation activities have taken several forms ranging from traditional securitisation transactions to different types of synthetic structures. Continuous studies for the establishment of international standards and harmonisation of national regulations for accounting and regulatory capital treatment of securitisation transactions, as constituent parts of International Accounting Standards and Basel II, resulted in a very complex and widely accepted framework for securitisation activities. Turkey has also been introduced to securitisation activities with future flow securitisation transactions backed by diversified payment rights, amounting to 4.3 billion as of June 2006. Preparation of a draft law on housing finance recently, which is establishing the legal and regulatory infrastructure for housing finance and a general securitisation framework has increased the appetite of Turkish banks for traditional ABS transactions. As a result of my analysis and overview of major concepts and developments both in a domestic and international context, some necessary actions have been addressed for a well functioning securitisation market and mitigation of major risks in Turkish banking sector. These actions can be summarised as; the maintenance of tax neutrality and bankruptcy remoteness of the domestic SPV like structures, provision of hedging opportunities through derivative transactions, limiting the level of government intervention, avoiding crowding-out effect of public borrowing requirements, establishment of domestic credit rating agencies and a national rating scale and structuring of some transactions in domestic currency. It is strongly believed that a successful implementation of securitisation together with a well functioning housing finance system will have important contributions to economic development and stability of Turkey.